2019
DOI: 10.1111/dom.13631
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of ertugliflozin in patients with type 2 diabetes mellitus inadequately controlled with metformin monotherapy: 104‐week VERTIS MET trial

Abstract: Aim To evaluate the long‐term efficacy and safety of ertugliflozin in adults with type 2 diabetes mellitus inadequately controlled on metformin. Materials and Methods A 104‐week Phase III, randomized double‐blind study with a 26‐week placebo‐controlled period (Phase A) and a 78‐week period (Phase B) where blinded glimepiride was added to non‐rescued placebo participants with fasting fingerstick glucose ≥6.1 mmol/L. Results through week 104 are reported. Results Mean (standard error) change in HbA1c from baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 21 publications
4
48
0
Order By: Relevance
“…Informed consent was obtained from individuals in each study. The designs for the two studies have been previously published [21][22][23][24] and are summarised in ESM Table 1. Both studies had two treatment phases and a treatment period of 104 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Informed consent was obtained from individuals in each study. The designs for the two studies have been previously published [21][22][23][24] and are summarised in ESM Table 1. Both studies had two treatment phases and a treatment period of 104 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…In Phase B, participants who had a fasting capillary glucose ≥6.1 mmol/l and were not rescued during Phase A had the addition of blinded glimepiride (for participants randomised to placebo) or glimepiride placebo (for participants randomised to ertugliflozin). Overall, 621 participants were randomised at the start of the study (209, 207 and 205 patients in the placebo, ertugliflozin 5 mg and ertugliflozin 15 mg groups, respectively), and 581 participants entered Phase B (190, 201 and 190 participants in the glimepiride, ertugliflozin 5 mg and ertugliflozin 15 mg groups, respectively) and received ≥1 dose of study medication in Phase B [21]. The VERTIS SU study comprised a double-blind, active-controlled, 52 week treatment period (Phase A), with a double-blind, activecontrolled 52 week treatment extension period (Phase B; ESM Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This current research is a double blinded, randomized, and prospective trial to determine the influences of the dapagliflozin on the cardiovascular results of type 2 diabetes. [ 24 , 25 ] We assumed that adding the dapagliflozin to the medication in the type 2 diabetes patients would reduce CVD risk and achieve the goal of glycemic control. [ 26 , 27 ]…”
Section: Introductionmentioning
confidence: 99%
“…18 Coadministration of ertugliflozin and metformin in a phase 1 study showed that there were no changes in pharmacokinetics (PK) compared with either agent administered alone. 9 The 2 agents have also been coadministered in phase 3 trials, 12,13,[19][20][21] and ertugliflozin given on a background of metformin was well toler-ated and reduced A 1C , fasting plasma glucose, body weight, and blood pressure compared with metformin alone. 12 Fixed-dose combination (FDC) formulations of ertugliflozin plus immediate-release metformin are available, with tablets containing ertugliflozin/metformin 2.5 mg/500 mg, 2.5 mg/1000 mg, 7.5 mg/500 mg, and 7.5 mg/1000 mg (in the United States) or 2.5 mg/850 mg, 2.5 mg/1000 mg, 7.5 mg/850 mg, and 7.5 mg/1000 mg (in the European Union).…”
mentioning
confidence: 99%